2013
DOI: 10.1017/s1092852913000424
|View full text |Cite
|
Sign up to set email alerts
|

Spatial behavior reflects the mental disorder in OCD patients with and without comorbid schizophrenia

Abstract: It seems as if both the OCD patients' focus on specific thoughts, and the contrasting wandering thoughts of schizophrenia patients, are reflected in the focused activity of the former and wandering from one place to the next of the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Furthermore, patients with severe OCD tend to exhibit depressive symptoms, elaborate avoidance behavior, and high levels of anhedonia, all of which consistent with decreased general activity. Finally, it has been reported that OCD patients move around less in their homes during everyday life compared to healthy controls (42). However, whether diminished general activity is an underexplored symptom of OCD that could potentially be studied in SAPAP3 -/will have to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, patients with severe OCD tend to exhibit depressive symptoms, elaborate avoidance behavior, and high levels of anhedonia, all of which consistent with decreased general activity. Finally, it has been reported that OCD patients move around less in their homes during everyday life compared to healthy controls (42). However, whether diminished general activity is an underexplored symptom of OCD that could potentially be studied in SAPAP3 -/will have to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Although we focused on minimizing the potentially confounding effects of decreased SAPAP3 -/general activity on reversal learning, it cannot be excluded as a trait of potential OCD relevance. For instance, OCD shows high comorbidity with depression and anhedonia (40)(41)(42), pathologies that produce decreased activity marked by loss of motivation and inability to experience pleasure. Furthermore, patients with severe OCD tend to exhibit depressive symptoms, elaborate avoidance behavior, and high levels of anhedonia, all of which consistent with decreased general activity.…”
Section: Discussionmentioning
confidence: 99%
“…From Gershoni et al (2013). stationary whereas Schizo-OCD patients wandered around a large space while performing the same motor task, as illustrated in Fig.…”
Section: Extending the Ocd Study To Comorbid Ocd And Schizophreniamentioning
confidence: 97%
“…This is somewhat in contrast with the behavior of the quinpirole rats, which involves excessive traveling along the same path (Szechtman et al, 1994). Nonetheless, an example of the use of trajectories to characterize mental disorders is found in a comparison of patients suffering from pure OCD and patients suffering from comorbid schizophrenia and OCD (Schizo-OCD) (Gershoni et al, 2013). That study was based on comparing 10 motor tasks (e.g., leaving the house, cleaning a rug, etc.)…”
Section: Extending the Ocd Study To Comorbid Ocd And Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation